Determining the effect of acute and chronic passive heating on endothelial and muscular function and the response of serum heat shock proteins - Didier, Kaylin Dix (Kansas State University, 2020)
Passive heating has been utilized as a therapeutic intervention for skeletal muscle disorders and improvements in cardiovascular function. Despite the growing body of research in the field of passive heating interventions, the underlying mechanisms for the physiological changes and the performance outcomes are not fully understood. The overarching aim of this dissertation was to determine the effect of acute and chronic whole-body heat treatments on endothelial and muscular function, exercise tolerance, and to determine the time course response of heat shock proteins (HSPs). In our first investigation (Chapter 2), we found that one bout of whole-body heating improved endothelial function measured by flow-mediated dilation. However, our data showed that the expression of HSP90α was not affect ~24 hours post the heat treatment. In the second investigation (Chapter 3) we found that one bout of whole-body passive heating was not a sufficient stimulus to produce changes in exercise tolerance (duration) during isometric knee extension at 40% maximal voluntary contraction. Furthermore, we demonstrated that neuromuscular recovery from exercise was not impacted by the heat treatment. However, we did find that diffusive oxygen delivery into the muscle during exercise was significantly decreased after heating. The third investigation (Chapter 4) was aimed at determining the effects of eleven consecutive days of whole-body passive heating on endothelial function, exercise tolerance, and the time course of HSPs over the chronic heating treatments. We demonstrated that the repeated bouts of heating did not improve endothelial function or exercise tolerance. However, during the vascular occlusion test we found that the perfusive and diffusive components of oxygen delivery in to the skeletal muscle were accelerated. The findings of these studies together indicate that physiological changes are occurring post passive heating, however these changes are not enough sufficient to increase exercise tolerance or performance. This dissertation contributes to the growing body of research on passive heat treatments and underlying mechanisms as an intervention for improving exercise tolerance.
Keywords: Heat shock proteins; Neuromuscular recovery; Endothelial function; Exercise tolerance